Universities trailing behind: Unquestioned epistemological foundations constraining the transition to online instructional delivery and learning - Dlamini, R.; Ndzinisa, N. (South African Journal of Higher Education, 2020)
Universities across South Africa have positioned learning management systems (LMS) as central to remote teaching and learning in response to COVID-19. This fundamentally challenges traditional teaching and learning practices where lecturers typically have close personal contact with students. Our argument is underpinned by critical discourse analysis and social constructivist pedagogy to gain deeper insights into the dimensions of LMS pedagogical affordances and the notion of equitable access to tertiary education in the midst of COVID-19 and the subsequent education and economic depression. Conducting a social constructivist pedagogy inspired analytical argumentative evaluation, we interrogate how digital technologies and platforms challenge the status quo and then argue on the systemic deficits of placing LMS at the centre of the transition in the hope of automatically cultivating an equitable learning environment to enable ubiquitous learning. Our analysis highlights potential contradictions in universities’ reliance on lecturers’ ingenuity without developing enabling structures supporting digital pedagogies at grassroots. This is to ensure inclusivity and avoid creating systemic inequalities that affect individual students’ experiences.